"Sternum-Into-Abdomen" Deformity With Abdominal Compression Following Osteoporotic Vertebral Compression Fractures Managed By 2-Level Vertebral Column Resection and Reconstruction. Issue 18 (15th September 2015) - Krishnakumar, R.; Lenke, Lawrence G.
Abstract : Study Design: A unique case report. Objective: To report a case of severe thoracolumbar kyphosis with abdominal compression causing gastric disturbance after treatment of an osteoporotic vertebral compression fracture and its ultimate management by vertebral column resection (VCR). We propose a new terminology "sternum-into-abdomen deformity" to describe this condition. Summary of Background Data: Management of osteoporotic vertebral compression fractures mainly aims at pain control and deformity reduction. VCR for decreasing abdominal compression due to the development of severe kyphosis after treatment of osteoporotic compression fractures has never been reported in the literature to our knowledge. Methods: This is a case report on a single patient. The hospital and office charts were reviewed. Reports of prior treatment of his compression fracture were analyzed. Results: This 73-year-old cachectic patient underwent vertebroplasty for a midthoracic compression fracture with progressive, severe kyphosis. His condition worsened and spinal reconstruction with a 2-level VCR restored more normal sagittal alignment and decreased his gastric compression. His back pain decreased and his ability to tolerate oral intake returned. Conclusion: We propose the term "sternum-into-abdomen deformity" to describe this type of severe kyphosis with abdominal compression. Treatment with a VCR and fusion for realignment of focal kyphosis can improve the quality of life for patients with this condition. Level of Evidence: 5 Abstract : This case report describes a patient with severe thoracic kyphosis after a vertebroplasty for an osteoporotic compression fracture. As his kyphosis progressed, his sternum was impinging on his abdomen, causing severe gastric compression and a weight loss of 25 lb. He successfully underwent a 2-level vertebral column resection and spinal fusion.